2017
DOI: 10.1097/md.0000000000006229
|View full text |Cite
|
Sign up to set email alerts
|

No association between metformin use and survival in patients with pancreatic cancer

Abstract: Several studies have suggested an association between use of metformin and an increased overall survival in patients diagnosed with pancreatic cancer, however with several important methodological limitations. The aim of the study was to assess the association between overall survival, pancreatic cancer, and metformin use.A retrospective cohort study of 1111 patients with pancreatic cancer was conducted using data from The Netherlands Comprehensive Cancer Organization (1998–2011). Data were linked to the PHARM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
1
23
0
3
Order By: Relevance
“…Cumulative evidence from cohort studies does not support a beneficial effect of metformin on pancreatic cancer survival. In the present study, the pooled RR from the six cohort studies not subject to immortal time bias was 0.93 (95% CI 0.82, 1.05; p = 0.22). These findings concur with data from clinical trials: three Phase II clinical trials did not found significant improvement in pancreatic cancer survival with adjuvant metformin therapy .…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Cumulative evidence from cohort studies does not support a beneficial effect of metformin on pancreatic cancer survival. In the present study, the pooled RR from the six cohort studies not subject to immortal time bias was 0.93 (95% CI 0.82, 1.05; p = 0.22). These findings concur with data from clinical trials: three Phase II clinical trials did not found significant improvement in pancreatic cancer survival with adjuvant metformin therapy .…”
Section: Discussionmentioning
confidence: 41%
“…b ) or from the Begg's test ( p = 0.71) or Egger's test ( p = 0.81). In contrast, pooled effect estimate from the nine studies subject to immortal time bias showed metformin was associated with lower mortality risk in pancreatic cancer patients (RR 0.76, 95% CI 0.69, 0.84; p < 0.001; Fig. c ).…”
Section: Resultsmentioning
confidence: 80%
“…Moreover, the pooling analysis by Zhang et al indicated that metformin may improve the survival for cancer patients with concurrent diabetes, particularly for breast, colorectal, ovarian, and endometrial cancer, but they failed to show such survival benefit in pancreatic cancer with only 3 studies included (HR=0.80, 95% CI= 0.62-1.03) [14]. Additionally, a recent meta-analysis combining 27 studies comprising 24178 participants was conducted to qualify the adjuvant effect of metformin in cancers, suggesting a better survival, particularly in colorectal and prostate cancer, however without special attention to pancreatic cancer Reni,2016 [26] Italy ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Lee,2016 [27] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Ambe,2016 [21] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cheon,2014 [28] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Hwang,2013 [29] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Amin,2016 [30] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Kordes,2015 [31] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Chaiteerakij,2016 [32] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Sadeghi,2012 [33] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cerullo,2016 [34] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Kozak,2016 [35] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Toomey,2015 [36] USA ▲ ▲ ▲ ▲ ▲ 5 Choi,2015 [37] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Beg,2017 [38] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Jang,2017 [39] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Frouws,2017 [40] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 E,2017 [41] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 [46] and by E et al (6 studies with 12,057 participants) have represented similar findings with demonstrating a survival benefit of metformin therapy for pancreatic cancer patients [47]. Furthermore, the subgroup analyses based on ethnicity in the current study revealed a more favorable prognosis for metformin therapy in Asian population (HR=0.74, P=0.01) but not evident in Caucasian population (HR= 0.92, P=0.10) which was in line with the findings by Zhou et al, indicating that ethnicity variation may contribute to the metformin action, however, the underlying mechanism for the discrepancy remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…The four meta-analyses include a total of 15 unique studies (13 observational and 2 RCTs); and conclude that metformin in comparison to nonmetformin users in PDAC is associated with relative benefit in overall survival in observational studies, but not in randomized controlled studies [2932]. In contrast, Frouws et al , who analyzed 907 patients with PDAC-DM, including 77 patients treated with metformin reported no survival benefit in patients with metformin use compared to non-users [33]. However, this study was limited by small proportion of patients with treatment on ADMs.…”
Section: Effect Of Metformin On Pdac Survivalmentioning
confidence: 99%